Pengaruh Kualitas Pelayanan, Harga dan Promosi terhadap Keputusaan Pembelian Minuman Cocktail di Hotel Gran Melia - Dava Syach Alhufi; Salman Paludi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Abstract: This study aims to analyze the influence of service quality, price, and promotion on purchasing decisions for cocktails at the Gran Melia Hotel. This study uses a quantitative approach with a survey method by distributing questionnaires to 125 respondents who are hotel customers and have purchased cocktails. The sampling technique used is Accidental Sampling. The collected data were then processed using SPSS software version 26, with a multiple linear regression analysis method. The results of the study indicate that service quality, price, and promotion have a positive and significant influence on purchasing decisions, both partially and simultaneously. This means that the better the quality of service, the more competitive the price, and the more effective the promotion carried out, the consumer's purchasing decision for cocktails will also increase. This finding has an important impact on the management of the Gran Melia Hotel in designing a more targeted marketing strategy. By considering the third variable, the hotel can increase customer satisfaction while encouraging increased cocktail sales. This study is expected to be a reference in making strategic decisions in the field of beverage marketing.